5PSQ-071 An adverse drug reaction in a paediatric patient with Dravet syndrome: cannabidiol and valproate drug–drug interaction. (24th March 2020) - Ortenzi, GB; Cesaroni, E; Berardi, MA; Garzone, AMF; Andresciani, E; Polidori, C; Pompilio, A
Abstract : Background and importance: Cannabis based therapies have been used to treat epilepsy for millennia, but in the past few years several studies have led to the marketing in Europe of a drug based on cannabidiol with an indication for Lennox–Gastaut and Dravet syndrome, authorised in Italy on compassionate use. Aim and objectives: The aim of this study was to describe an adverse drug reaction (ADR) in a patient with Dravet syndrome treated with cannabidiol oral solution. Material and methods: Periodic reports required by the compassionate use protocol and pharmacovigilance activity were used to collect the data. Results: The patient fulfilled all eligibility criteria: female patient born in January 2001, body weight 60 kg, diagnosed with Dravet syndrome and inadequate seizure control with standard therapy (valproic acid (VPA) 600 mg/day, clobazam 20 mg/day and stiripentol 2000 mg/day). In January 2019, cannabidiol oral solution 100 mg/mL was added to the therapy, after a favourable opinion by the ethics committee and informed consent was obtained. The following dosing schedule was used: 5 mg/kg/day for 7 days and 10 mg/kg/day for 7 days, and a maintenance dose of 15 mg/kg/day. In February 2019, an adverse reaction was reported: increased hepatic enzymes AST 151U/L (0–40), ALT 45 U/L (0–40), blood levels of VPA 115.2 µg/mL (50–100) and decreased platelet count 126 × 10 3 /mmc (150–400). In March 2019, hepatic enzyme levels decreased (AST 78 U/L, ALT 24 U/L) but platelet count decreased further to 98×10 3 /mmc (150–400) and blood levels of VPA increased (129.7 µg/mL). The physician considered reducing the daily dose of VPA to 10 mg/kg/day. In June 2019, platelet count was 187×10 3 /mmc (150–400) and VPA 101.8 µg/mL (50–100). The Naranjo algorithm, with a result of 7, determined the event related to cannabidiol/valproic acid as 'probable'. Conclusion and relevance: The interaction between VPA and CBD has already been reported in the literature with strong evidence in favour of hepatocellular toxicity but there is no evidence regarding the modification to platelet count. The strict management of the drug was critical to minimise the collateral effects. Cannabidiol therapy did not produce detectable effects on the management of seizures, but the therapy was not suspended thanks to a detectable increase in the patient's cognitive and social capacities. References and/or acknowledgements: www.micromedexsolutions.com access on 19/11/2019 No conflict of interest.